2016
DOI: 10.1109/tnsre.2015.2498973
|View full text |Cite
|
Sign up to set email alerts
|

Seizure Suppression Efficacy of Closed-Loop Versus Open-Loop Deep Brain Stimulation in a Rodent Model of Epilepsy

Abstract: We assess and compare the effects of both closed-loop and open-loop neurostimulation of the rat hippocampus by means of a custom low-power programmable therapeutic neurostimulation device on the suppression of spontaneous seizures in a rodent model of epilepsy. Chronic seizures were induced by intraperitoneal kainic acid injection. Two bipolar electrodes were implanted into the CA1 regions of both hippocampi. The electrodes were connected to the custom-built programmable therapeutic neurostimulation device tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
57
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(59 citation statements)
references
References 45 publications
1
57
0
1
Order By: Relevance
“…If we ignore the analytical results and try to control epileptiform activity using, instead of the aforementioned dynamically-guided closed-loop method to stop seizure generation, an open-loop protocol—which is the normal paradigm in most of clinical DBS applications (but see Morrell, 2011)—we will find that same stimulation protocol (5 seconds at 5 Hz) reduces seizure frequency by 17%, compared with the ~90% reduction using the closed-loop system (Salam et al, 2016). It is fair to note that other studies using periodic pacing without a closed-loop approach found greater success rate at stopping seizures, even though in these cases the stimulation was applied for longer times (Barbarosie and Avoli, 1997; Panuccio et al, 2013).…”
Section: A Dynamiceutical Illustration: Similar Approach To Brain Andmentioning
confidence: 99%
See 1 more Smart Citation
“…If we ignore the analytical results and try to control epileptiform activity using, instead of the aforementioned dynamically-guided closed-loop method to stop seizure generation, an open-loop protocol—which is the normal paradigm in most of clinical DBS applications (but see Morrell, 2011)—we will find that same stimulation protocol (5 seconds at 5 Hz) reduces seizure frequency by 17%, compared with the ~90% reduction using the closed-loop system (Salam et al, 2016). It is fair to note that other studies using periodic pacing without a closed-loop approach found greater success rate at stopping seizures, even though in these cases the stimulation was applied for longer times (Barbarosie and Avoli, 1997; Panuccio et al, 2013).…”
Section: A Dynamiceutical Illustration: Similar Approach To Brain Andmentioning
confidence: 99%
“…The reason that such a short stimulation in the previous studies (5 seconds) was efficient at preventing seizure generation is probably due to the typical extreme sensitivity to perturbations when a system is close to a dynamical bifurcation, as was elaborated in our publications. Such a short precisely-timed stimulus has the added advantage of these closed-loop methods in that they deliver less energy than conventional open-loop stimulation (Salam et al, 2016; Cagnan et al, 2017). …”
Section: A Dynamiceutical Illustration: Similar Approach To Brain Andmentioning
confidence: 99%
“…Seizure detection is another application of FBC and EBC [26][27][28][29][30][31][32][33][34][35][36]. In [26,27], total information outflow based on the DTF and PDC considered as feature and SVM is a classifier, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Said differently, these closed‐loop DBS systems could record and use the neural states of a patient to influence the device's stimulatory behavior. This change in stimulation pattern was an improvement over the traditionally constant stimulation patterns of open‐loop DBS devices in that the closed‐loop devices provide stimulation only when needed and simultaneously save battery power 4 . If the stimulation pattern of an open‐loop device needed adjustment, then a health care provider or consult programmer would have to change it manually.…”
mentioning
confidence: 99%
“…This change in stimulation pattern was an improvement over the traditionally constant stimulation patterns of open-loop DBS devices in that the closed-loop devices provide stimulation only when needed and simultaneously save battery power. 4 If the stimulation pattern of an open-loop device needed adjustment, then a health care provider or consult programmer would have to change it manually. By contrast, closed-loop DBS stimulation patterns are the result of a personalized algorithm within the device that interprets the neural data and systematically determines when stimulation is needed.…”
mentioning
confidence: 99%